The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2018
DOI: 10.1039/c8cp04563a
|View full text |Cite
|
Sign up to set email alerts
|

Communication through the furan ring: the conformational effect on the internal rotation of 5-methyl furfural studied by microwave spectroscopy

Abstract: Internal rotation is a fundamental motion of methyl groups that provides important insights into the molecular physics of isolated molecules. The barrier heights of such large amplitude motions are highly sensitive to their molecular and electronic environment. To date, it is still not possible to accurately determine these values using quantum chemical calculations. To probe the effect of molecular conformations on the barrier heights of substituted furan rings, the molecular jet Fourier transform microwave s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 14 publications
(31 citation statements)
references
References 24 publications
(28 reference statements)
1
29
1
Order By: Relevance
“…7). Compared to the observation found for 2-acetylfuran ( 5 ) and its related molecules furfural ( 4 ), 66 methyl furfural 67 and 2-acetyl-5-methylfuran ( 6 ), 68 we found that the heteroatom in the ring significantly affects the conformational stability. The syn -conformer of 2-acetylfuran ( 5 ) is much higher in energy than the anti -conformer.…”
Section: Discussioncontrasting
confidence: 72%
“…7). Compared to the observation found for 2-acetylfuran ( 5 ) and its related molecules furfural ( 4 ), 66 methyl furfural 67 and 2-acetyl-5-methylfuran ( 6 ), 68 we found that the heteroatom in the ring significantly affects the conformational stability. The syn -conformer of 2-acetylfuran ( 5 ) is much higher in energy than the anti -conformer.…”
Section: Discussioncontrasting
confidence: 72%
“…The negative charges on the oxygen atoms of furfural (2) stabilizes the anti-conformer, while the syn-form is favored by the opposite charges on oxygen and sulfur or selenium atoms in 2TPC (1) and 2SeC (4) [67], as visualized also in Figure 8 with the charge data obtained from NBO calculations. A further example to support this argument is the stability of the anti-form in two furfural derivatives, methyl furfural (5) [68] and 2-acetyl-5-methylfuran ( 6) [69], where the anti-conformer (called cis in ref. [68]) is also 1.1 kJmol 1 and 4.19 kJmol 1 , respectively, lower in energy than the syn conformer (called trans in ref.…”
Section: Conformational Stabilitymentioning
confidence: 98%
“…A further example to support this argument is the stability of the anti-form in two furfural derivatives, methyl furfural (5) [68] and 2-acetyl-5-methylfuran ( 6) [69], where the anti-conformer (called cis in ref. [68]) is also 1.1 kJmol 1 and 4.19 kJmol 1 , respectively, lower in energy than the syn conformer (called trans in ref. [68]).…”
Section: Conformational Stabilitymentioning
confidence: 98%
See 1 more Smart Citation
“…The basis set was chosen to be either Dunning's cc-pVTZ [6] or Pople's 6-311+G(d,p) and 6-311++G(d,p) [7]. From our own experiences [8][9][10][11] and studies in the literature [12][13][14][15], the MP2/6-311G++(d,p) level of theory has proven its reliability in calculating rotational constants of aromatic-ring containing molecules for assignment purposes. Therefore, quantum chemical calculations at this level were carried out with the Gaussian 16 program [16] and the ab initio rotational constants A = 2819.5 MHz, B = 880.0 MHz, C = 670.7 MHz were used as starting values to predict the microwave spectrum of coumarin.…”
Section: Quantum Chemical Calculationsmentioning
confidence: 99%